Diabetic Retinopathy: A Growing Concern for Diabetes Patients in Indonesia - Prajnaparamita, Irfani (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Diabetic retinopathy (DR) is a serious complication of diabetes and one of the leading causes of blindness worldwide, including in Indonesia. As the prevalence of diabetes continues to rise, diabetic retinopathy has become an increasing public health concern, particularly due to the limited awareness, late diagnosis, and inadequate access to ophthalmic care. This study explores the growing burden of diabetic retinopathy among diabetes patients in Indonesia using a qualitative approach. Through in-depth interviews with healthcare professionals, diabetic patients, and public health officials, as well as an analysis of policy documents and health reports, this research examines the challenges faced in the prevention, early detection, and management of DR. Findings indicate that insufficient healthcare infrastructure, lack of trained specialists, and economic barriers significantly hinder access to timely eye examinations and treatment. Moreover, many diabetes patients have limited knowledge about the risks of DR, leading to delays in seeking medical intervention. The study also highlights the role of cultural perceptions and healthcare system inefficiencies in exacerbating the problem. It is evident that a more comprehensive strategy, involving government intervention, community awareness programs, and improvements in healthcare accessibility, is necessary to address this growing concern. Strengthening early screening programs, integrating ophthalmic care into primary healthcare services, and promoting better diabetes management practices are essential steps toward reducing the impact of DR in Indonesia. This research underscores the urgent need for a multi-sectoral approach to prevent vision impairment and improve the quality of life for diabetes patients.